Imaging-detected sports injuries and imaging-guided interventions in athletes during the 2022 FIFA football (soccer) World Cup - Marcelo Bordalo (17704395) (2023)
Objective To describe imaging-detected musculoskeletal injuries and image-guided interventional procedures during the 2022 FIFA football (soccer) World Cup. Materials and methods Retrospective analysis of all radiologic examinations performed in a central medical facility for athletes was performed by two board certified musculoskeletal radiologists. Data on muscle, tendon, ligament, cartilage, and bone injuries were collected according to imaging modality and body part. Results A total of 143 radiology examinations in 94 athletes were evaluated at the central medical facility. Magnetic resonance imaging (MRI) was the most utilized modality (67%), followed by radiography (12%), ultrasonography (9%), and computed tomography (4%). Image-guided interventions corresponded to 8% of all radiological examinations. There were 112 injuries described, affecting muscles and tendons (42%), ligaments (25%), cartilage (21%), and bone (12%). Most injured body parts were thigh (27%), foot and ankle (23%), knee (23%), and hip/groin (8%). Most injured players were within the age range of 24–35 years old (71%). Conclusion Imaging was utilized in 11% of players who participated in the 2022 FIFA World Cup in Qatar. MRI was the most utilized modality, and acute muscle tears were the most diagnosed type of injury. Summary Diagnostic imaging played an important role in diagnosing sports-related injuries during the 2022 FIFA World Cup. Other Information Published in: Skeletal Radiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00256-023-04451-z